Analysis of Factors Associated with the Ocular Features of Congenital Cataract Children in the Shanghai Pediatric Cataract Study - Wenwen He; Ting Sun; Jin Yang; Guoyou Qin; Zhenyu Wu; Xiangjia Zhu; Yi Lu (Journal of Ophthalmology)
Purpose. To investigate the ocular features of children with congenital cataract in a tertiary referral eye center in East China. Methods. We retrospectively reviewed the clinical data of congenital cataract children who underwent cataract surgery between April 2009 and April 2014 at the Eye and ENT Hospital of Fudan University and identified factors associated with the axial length (AXL) and corneal curvature (K value). Results. We included 493 children, 210 with unilateral and 283 with bilateral cataract. The mean AXL was 22.03 ± 1.97 mm and the mean K value was 43.61 ± 1.86 D. Age showed a linear correlation with AXL in unilateral cataract eyes and a logarithmic correlation with AXL in bilateral cataract eyes (both P<0.001). AXL was longer and the K value was smaller (both P<0.01) in boys than in girls after adjusting for age and cataract laterality. AXL was longer in unilateral cataract eyes than in bilateral cataract eyes after adjusting for age and gender (P=0.004). In children with unilateral cataract, AXL was significantly longer in the affected eye than in the contralateral eye (P<0.001). Conclusion. Age, gender, and cataract laterality together contribute to the development of ocular features of congenital cataract children, especially for AXL.